2019
DOI: 10.1016/j.bbmt.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Direct HLA Genetic Comparisons Identify Highly Matched Unrelated Donor-Recipient Pairs with Improved Transplantation Outcome

Abstract: HLA matching by allele-level genotyping is largely based on genetic similarity between a few exons that encode the antigen recognition domain (ARD) of the HLA protein. Next-generation sequencing (NGS) can identify HLA genetic polymorphisms in non-ARD-encoding exons, introns, and untranslated regions, but the impact of these polymorphisms on hematopoietic cell transplantation (HCT) outcome is unclear. We performed NGS-based sequencing of 11 HLA loci on a well-characterized retrospective cohort of 166 unrelated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
0
16
0
6
Order By: Relevance
“…Determining the sequence of HLA proteins expressed by a recipient or donor by exon typing without ambiguity in the second field is considered sufficient for current clinical practice . However, our understanding of the impact of polymorphisms in coding positions out of the peptide‐binding groove, in non‐coding regions on HLA expression, disease susceptibility, and transplantation outcomes is continuing to evolve, and new perspectives in terms of NGS applications are emerging . Moreover, nucleotide substitutions, insertions, and deletions in the enhancer–promoter, intron, and 3′‐UTR regions can result in null alleles requiring identification in clinical settings …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining the sequence of HLA proteins expressed by a recipient or donor by exon typing without ambiguity in the second field is considered sufficient for current clinical practice . However, our understanding of the impact of polymorphisms in coding positions out of the peptide‐binding groove, in non‐coding regions on HLA expression, disease susceptibility, and transplantation outcomes is continuing to evolve, and new perspectives in terms of NGS applications are emerging . Moreover, nucleotide substitutions, insertions, and deletions in the enhancer–promoter, intron, and 3′‐UTR regions can result in null alleles requiring identification in clinical settings …”
Section: Introductionmentioning
confidence: 99%
“…7 However, our understanding of the impact of polymorphisms in coding positions out of the peptide-binding groove, in non-coding regions on HLA expression, disease susceptibility, and transplantation outcomes is continuing to evolve, and new perspectives in terms of NGS applications are emerging. [9][10][11][12] Moreover, nucleotide substitutions, insertions, and deletions in the enhancer-promoter, intron, and 3 0 -UTR regions can result in null alleles requiring identification in clinical settings. 13 NGS methods are based principally on the following steps: immobilization of the DNA sample onto a solid support, cyclic sequencing reactions at the clonal level using automated fluidic devices, and detection of millions of simultaneous molecular events.…”
mentioning
confidence: 99%
“…в соответствии с современной номенклатурой HLA -на уровне 4-го поля, например, А*01:01:01:01 [16]. Подбор донора и реципиента при алло-ТГСК с аллельным разрешением, позволяющим выявлять генетические полиморфизмы вне экзонов, кодирующих пептидсвязывающие домены HLA-молекул, повышает выживаемость больных после алло-ТГСК [17,25]. Предполагают, что полиморфизмы в некодирующих областях HLA-генов являются маркерами HLA-гаплотипов [17,25].…”
Section: Introductionunclassified
“…Finally, it should be noted that previously published data on major histocompatibility complex haplotype matching, coupled with the accepted reduced risk of complications in related donor transplantation, suggest that greater compatibility of the HLA region is associated with better outcome. We also point out that since the acceptance and publication of our article, 2 independent studies (a published manuscript [1] and a presented abstract [2]) have also demonstrated the beneficial effect of matching for additional regions of the HLA gene on unrelated donor HCT outcome, suggesting these observations are not unique, and that there is much still to learn about the impact of genetic variation outside of the ARD on HCT outcome.…”
Section: To the Editormentioning
confidence: 94%